Systematic Analysis of Determinants of SME Performance in Indonesia: Integration of RBV Perspectives, Dynamic Capabilities, and Social Cognitive Theory - Muhammad Adil. MA; Yayan Hendayana (Green Publisher Indonesia, 2025)
SMEs are the main backbone of Indonesia's economy, but their performance is still limited by access to financing, low digital adoption, and limited managerial capacity. This article presents a systematic literature review to identify the development of SME performance in Indonesia, map the determinants of the sector, highlight the research gap, and formulate policy recommendations and research agendas. Theoretical synthesis includes Resource-Based View (RBV), External Resource/Institutional Theory, Dynamic Capabilities Theory, Social Cognitive Theory. The results of the study show that the performance of SMEs is synergistically influenced by internal factors (human resource competence, innovation, entrepreneurial orientation, and resource management), external factors (access to financing, policy support, partnerships, and digital technology), and managerial behavior (self-efficacy, social learning). Dynamic capabilities serve as a key mechanism that allows organizations to reconfigure internal, external resources to respond to environmental changes and drive sustainable performance. The contribution of this article is an integrative conceptual model and the basis for evidence-based management in SMEs. Practical implications emphasize strengthening internal capacity, expanding strategic networks, accelerating digital transformation, implementing a comprehensive performance management system, and triple helix collaboration. The main limitation lies in the absence of empirical tests and the dominance of cross-sectional cross-sectional studies. The next research is suggested to develop a multi-theory model that is tested longitudinally and quantitatively, delves into digital capabilities and organizational agility, and incorporates the local Indonesian context as a mediating or moderation variable.